The relationship between the risk of falling and fear of falling among aged hospitalized patients - Ali Dadgari; Hadi Hojati; Seyed Mohammad Mirrezaie (Tehran University of Medical Sciences, 2020)
Background & Aim: Identifying older people with the risk of falls in hospitals is particularly essential for the prevention of falls. Review of literature revealed that the association of falls and fear of falls had not been investigated extensively in previous studies in Iran. This study aimed to determine the relationship between falling and fear of falling among elderly hospitalized patients. Methods & Materials: In this descriptive-correlational study, 1123 subjects were recruited. Of all subjects, 385aged hospitalized patients, 60 years old and above, were conveniently selected based on inclusion criteria in Shahroud Imam Hossein hospital from March to December 2016. Johns Hopkins fall risk assessment tool (JHFRAT) was used to evaluate the risk of falls among older people and the Falling Efficiency Scale (FES) was applied to assess fear of falling. SPSS software version 19with the significance level of p<0.05. Chi-Square test and exact test of Fisher and logistic regression has been used for data analysis. Results: All aged patients (n=1123) admitted in the emergency room were assessed for eligibility to inclusion in the study.  Of all subjects, 385 patients were included in this study. The subjects' mean of age was 71.68±4.32 years, age range: 60-84. Of all samples (n=385) of study, 90 (23.4%), 151(39.2%), and 144 (37.4%) had low, middle, and high risk of falls, respectively. Of all participants of the study, 193(51%) subjects were male, and 192(49%) were female. One-third (36.4%) of the subjects had fear of falls and (33.8%) experienced fall in the last six months before admission. A statistically significant relationship was found between the incidence of falls and fear of falling (P<0.001). Conclusion: This study found JHFRAT and FES as two applicable instruments for assessment of aged people. The result of this study concluded that evaluation of fear of falling and the risk of falls among hospitalized elderly patients are recommended as a routine procedure to predict the risk of falls. Nurses are in the best position to evaluate the fear of falls and risk of falls, so it is recommended considering the fear of falls as a potential risk factor for falls in the hospital.